Waqf and Partnerships for the Goals (SDG-17): A Maqasid Framework - Rusydiana, Aam Slamet; Sukmana, Raditya; Laila, Nisful (SMART Insight, 2023)
The seventeenth Sustainable Development Goal encapsulates the topic on enhancing implementation tools and reviving the global partnership for sustainable development. Waqf, on the other hand, is an instrument of Islamic social finances that has a sustainable nature and is relevant to the SDGs; therefore, it has the potential to be utilized in the maintenance of partnerships to attain goals. This study aims to demonstrate the relevance of the waqf model to the SDGs by highlighting the waqf model applicable in Indonesia, which is in line with SDG 17 from a Maqasid Syariah perspective. The results indicate that the global cash waqf model is the appropriate funding to meet the seventeenth objective, which is the maintenance of international partnerships